A Megalithic Circle from Ǝmba Dǝrho: Some Significant Aspects of Culture - Rao, S. Krishna; Libsekal, Yosief (Aethiopica, 2004)
The archeological evidence of megalithic stone circles at Ǝmba Dǝrho sheds some light on the development of prehistoric religion, with particular regard to death and burial. With the exception of slight changes from the prehistoric era, the material culture of megalithic burial at Ǝmba Dǝrho reflects the prehistoric tradition. It is thus direct proof of an historical continuum of prehistoric religion. An interesting aspect of the finds at Ǝmba Dǝrho concerns the evidence of cowry shells and teeth. The Eastern Cushitic speaking community – the Saho, who claim to have descended from the ʿAfar – trade cowry shells and are involved in certain smuggling activities on the coast with Saudi Arabia. It is therefore logical to assume that the builders of the megalithic circles at Ǝmba Dǝrho may also have been involved in similar activities. The type of pottery found at the burial site suggests it was used by an individual and associated with different routine activities during his lifetime. In Ǝmba Dǝrho two types of megalithic circles were found: single stone circles, and double stone circles (an inner circle within a larger circle); these may have been arranged by two different groups. Such differences, however, could also have been the result of the influence of micro-environmental variations within the same ecological zone. With regard to the ethnicity and origins of megalithic circles, there exists a general disagreement. A few hundred megalithic burial sites were excavated in India. Some scholars suggest they have Celtic or Scythian origins, and others suggest Iranian origins, but it is only a few that emphasize indigenous Dravidian origin on the basis of living megalithic traditions (Deo 1978: 451). With the discovery of megalithic stone circles in Eritrea and other parts of Africa, we now have new examples of indigenous origins reflected in living traditions. ATTENTION: Due to copy-right no online publication is provided.